KERJASAMA PEMERINTAH DENGAN PIHAK SWASTA, MASYARAKAT DAN ANTAR PEMERINTAH DALAM PENANGANAN PENCEMARAN LIMBAH BATIK DI KOTA PEKALONGAN PADA TAHUN 2015 - Cavandhes, Ayu; Yuwono, Teguh; Harsasto, Priyatno (Journal of Politic and Government Studies, 2017)
Batik industry is an industry that many exist in Pekalongan city, theexistence of batik industry are produces waste from the process of making batik.There are two possibilities to dispose the batik waste, there are processed first anddiposed directly without processing that will cause pollution. The purpose of thisresearch are to identify the patterns of inter-governmental cooperation, andgovernment with private and community in overcoming the problem of batik wastepollution, and to know the success rate ofcooperation patterns that has been doneto overcome the problem of batik waste pollution.The method of the research is used qualitative approach with data collectiontechnique that consist of observation, interview, and documentation. Informants inthis research are head of Environmental Section and Environmental LawArrangement of Environmental Department (DLH) Pekalongan city, Head ofPollution Control and Damage Section of DLH Pekalongan city, Head of wastepollution control section of DLH Pekalongan city, the private sector there is batikcraftsmen, and the community there is environmental care community.The result of the study indicate that 1) The pattern of inter-governmentalcooperation is for funding the manufacture of IPAL, 2) The pattern of governmentcooperation with the privat sector (batik craftsmen) is divison the authority, that isgovernment facilitates the construction of IPAL and provides land, whereas batikcraftsmen are obliged to maintain and operate the IPAL, 3) The pattern ofgovernment cooperation with the community is the community independentlyprovide assistance for the construction of IPAL, while the government did thecoaching, supervision, assistances, and providing moral support. 4) Theimplementation of cooperation in overcoming the pollution of batik wate inPekalongan city has not effectively.Keywords : Cooperation, Pollution of Batik Waste